The Model for Storing Tokens in Local Storage (Cookies) Using JSON Web Token (JWT) with HMAC (Hash-based Message Authentication Code) in E-Learning Systems - Joeharsyah Reza; Asep Marzuki; Syabdan Dalimunthe (Journal of Applied Engineering and Technological Science (JAETS), 2022)
E-learning is a technology that may be used in the learning process to improve not only the distribution of learning materials but also the ability of learners to modify their abilities of various competencies contained in a database. A Web Service is used to integrate the data. Web Service is a set of standards and programming methods for sharing data between different software applications, distributing services over the internet that supports system interoperability. In this digital era, the system that will survive is one that can function on multiple platforms, and one of the options is to use web servicess. Data is exchanged in JSON format, and JSON Web Tokens are used for authentication security (JWT). The use of JWT for token-based authentication on web services can help overcome interoperability issues. JWT is stateless and allows for the inclusion of data in the token authorisation. JWT includes a number of algorithm possibilities, including HMAC. Overall, the adoption of HMAC outperforms the criteria of token generation time, token size, and token transfer speed. Storing JSON Web Token into local storage in the client browser using the HMAC algorithm has been presented in this paper. The proposed work has shown that JWTs do not need to be stored on the server but can be stored on the client browser side using local storage.